Article Effectiveness of Instruction Program on Caregiver Knowledge concerning Emergency Care for Geriatrics at Geriatric Home in Baghdad City. - Ibrahim, ali; hassan, huda (Iraqi National Journal of Nursing Specialties, 2019)
Objectives: The aim of the study is to evaluate the information of caregivers concerned emergency care for the elderly and to identify the relationship between caregiver information and their educational level, years of service and training courses. Methodology: A quasi-experimental study was conducted in the Geriatric Care Home in Baghdad City (the governmental and private geriatric care home ) for the period from October, 14th , 2018 to March, 20th , 2019 to find the effectiveness of the instructional program on caregivers knowledge about emergency care for the elderly.. A purposive sample (non-probability) was consisting of (30) males and females caregivers, the sample was selected from geriatric care home in Baghdad city .To implement the program an instrument was used to collect caregiver’ data which consist of two parts: The first part concerns demographic information for caregivers. and the second part involves two domains involving (48) items concerning caregiver knowledge about physiological changes and health problems and their knowledge about emergency care for older persons .The instrument was authenticated by through a panel of ten expert. The researcher used SPSS version 20 to analyze the data, and applying the descriptive and inferential statistical analysis. Results: The results of the pre-test for caregivers in a government and private geriatric care home revealed that caregivers ’knowledge about physiological changes and health problems as well as emergency care was moderate , while post-test results showed that caregivers’ knowledge about physiological changes and health problems as well as emergency care had improved to high level because of the positive impact of the instruction program. The study founded that there was correlation between the effectiveness of the instruction program on caregiver knowledge, and the demographic information including gender , age, social status, monthly income and race . The result of study retreaded that there were a significant relationship between the effectiveness of the instruction program and the caregiver years of experience, the educational level, the training courses and the occurrence of emergencies at P≤0.05. Recommendation: The study recommends to increase the training courses inside and outside Iraq for caregiver and encouraged them to use safety measures to avoid the injury of elderly persons.